Kebijakan Pengembangan Perikanan Tangkap Melalui Analisis SWOT Dan Analytic Hierarchy Process (AHP) Di Kabupaten Buleleng, Bali - I Ketut Wija Negara; Endang Wulandari Suryaningtyas; Made Ayu Pratiwi; I Gede Wahyu Suryawirawan; Kadek Adi Chandra Kusuma; Perdana Rizky Khalista; John Lynham (Journal of Marine and Aquatic Sciences, 2023)
Buleleng Regency has large fisheries and marine potential, including the capture fisheries sector. Optimal capture fisheries management will be able to provide welfare for community groups that depend on fishing for their lives. This research aims to formulate a policy strategy for the development of capture fisheries in Buleleng Regency. This research was conducted on 15 May - 31 October 2020. The locations for collecting data for respondents were 7 (seven) Districts and 2 (two) Villages in each District in Buleleng Regency. A quantitative descriptive research approach combines SWOT analysis and Analytic Hierarchy Process (AHP). The results of the analysis obtained Progressive Strategy (SO) with a value of x: 0.2 and y: 0.6. This strategy includes the quality of catches, fishing industry areas, coaching and mentoring of fishermen, utilization of fishing ports, fishing business capital, fishing units, and fisherman insurance. The results of the Consistency Ratio (CR) value calculation show a figure of 0.03, which means that the assessment of the strategy criteria is acceptable. The results of the analysis of the policy criteria hierarchy of the Analytic Hierarchy Process (AHP) obtained 5 (five) priority strategies that need to be implemented in collaboration at each level of authority from the Provincial Government of Bali or the Bueleleng Regency Government, namely modernizing fishing units, ensuring the safety and health of fishermen's families through equal distribution of fishermen's insurance receipts, facilitating fishermen's business capital through capital institutions, increasing fishermen's skills and knowledge regarding modernization of technology-based fishing techniques, and utilizing the Sangsit Fish Landing Base (PPI) as the leading center for capture fisheries activities in Buleleng.